2006
DOI: 10.1111/j.1365-3083.2006.01836.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined Costimulation Blockade Prevents Rejection of Allogeneic Islets in Mice

Abstract: There is a need for immunosuppressive protocols in islet transplantation that are neither nephrotoxic nor diabetogenic. We have examined blockade of the CD28‐B7, CD40‐CD40L and ICAM‐LFA‐1 pathways in a model of allogeneic islet transplantation in mice to determine the efficacy of this blockade in prolongation of graft survival. Histological evidences of inflammation and function were evaluated in grafts that had been functioning for 100 days. Treatment with a combination of all three drugs, or with CTLA4Ig and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The sections were then incubated with biotin‐conjugated goat anti‐rat IgG after pre‐diluted strepavidin‐HRP was added, and the slides were exposed to diaminobenzidine (DAB). The amount of islet degeneration/destruction was assessed semiquantitatively as follows: 0 = no degeneration, 1 = ≤1 apoptosis/100 islets, 2 = ≤ 2 apoptosis/100 islets, 3 = one focus of islet destruction and 4 = ≥ 2 foci of islet destruction [20].…”
Section: Methodsmentioning
confidence: 99%
“…The sections were then incubated with biotin‐conjugated goat anti‐rat IgG after pre‐diluted strepavidin‐HRP was added, and the slides were exposed to diaminobenzidine (DAB). The amount of islet degeneration/destruction was assessed semiquantitatively as follows: 0 = no degeneration, 1 = ≤1 apoptosis/100 islets, 2 = ≤ 2 apoptosis/100 islets, 3 = one focus of islet destruction and 4 = ≥ 2 foci of islet destruction [20].…”
Section: Methodsmentioning
confidence: 99%
“…The role of anti‐CD154 in preventing organ transplant rejection is well known [11]. The lymphocyte function–associated antigen 1 (LFA‐1)/intercellular adhesion molecule‐1 (ICAM‐1) pathway plays an important role in the activation and proliferation of naïve T cells, especially CD8 + T cells [12, 13], and the combination of anti‐LFA‐1 and anti‐CD154 induces tolerance of primary allografts in mice [14, 15]. It has been reported that the OX40/OX40L pathway plays a critical role in the activation and proliferation of CD4 + memory T cells [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…anti-CD154 induces tolerance of primary allografts in mice [14,15]. It has been reported that the OX40 ⁄ OX40L pathway plays a critical role in the activation and proliferation of CD4 + memory T cells [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Compound (Cpd) K, as a ginseng metabolite, is a synthesized analog of highly unsaturated fatty acids of Isatis tinctoria L. (27,36). The therapeutic effect of Cpd K in diabetic mice shows that Cpd K significantly prolongs islet allograft survival with minimal adverse effects after 10 days.…”
Section: Compound Kmentioning
confidence: 99%